Kritik Hadis Zikir Berjama'ah - febriyeni febriyeni (Islam Transformatif : Journal of Islamic Studies, 2018)
It is still a debate by Muslims community about the right practice of the dhikr, because the explanation in the Qur’an of the issue of dhikr is very common. Meanwhile the hadith of the Prophet provides also various information about this issue. The guidance of the hadith about the practice of dhikr relies on the practice which is done by the Prophet, then emulated and imitated by his friends and became the practice of sunna for Muslims until today. One of the issues sahabah is the implementation of zikr in congregation (dhikr jama'i). Dhikr in congregation is gathering some people with one voice chanting dhikr. There are pros and cons regarding this practice of Dhikr. There are groups who think that the congregation of Dhikr is an act of heresy and in contrast, there is a presumption that the act is sunnah. This paper will discuss the issue, seen from the perspective of Hadith. This research uses library research method by reviewing the hadiths related to the congregation of Dhikr followed by the criticism of Hadiths’ Sanad and Matan, and the understanding of those hadiths.